Understanding Suicidal Behavior Using a Comprehensive Approach. (April 2023) - Chelmardi, Ahmadreza Kiani; Rashid, Sajjad; Dadfar, Mahboubeh; Lester, David
A comprehensive understanding of how suicidal risk factors interact with one another to increase the frequency of suicide ideation and attempted suicide is critical for improving theoretical models of suicide and prevention efforts. The aim of the present study was to explore the prediction of suicide ideation formation and its transition to suicide attempt through the interactions of the constructs suggested by the IPTS, IMV and 3ST theories, as well as other clinical factors. The core constructs of several theoretical models were assessed using a battery of scales administered to 909 Iranian college students. The results supported Klonsky's 3ST and O'Connor's IMV models and, in addition, the relevance of non-suicidal self-injury, the acquired capacity for self-harm, sexual abuse, and exposure to family self-harm for the transition from suicide ideation to a suicide attempt. Depression and PTSD were background factors rather than risk factors for suicide ideation or suicide attempt. Limitations were that the information provided by students may have been biased due to the stigma surrounding suicide in Iranian culture, and the proportion of female students was high.